2021
DOI: 10.1016/j.jsurg.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Home Field Advantage: Assessing the Geographic Trends of the Plastic Surgery Residency Match during the COVID-19 Pandemic

Abstract: Objective In previous plastic surgery residency match cycles, in-person activities at other institutions, such as away rotations, have facilitated matches outside of an applicant's home program or region. The COVID-19 pandemic, however, limited these in-person opportunities. Therefore, we hypothesized that applicants of the 2021 cycle would be more likely to match into programs with which they have existing geographic connections when compared to previous years. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 16 publications
3
38
0
Order By: Relevance
“…All 3 studies concluded that lack of face-to-face interaction, such as virtual interviews and lack of away rotations, may have played a role in their observed findings. Although correlation does not equal causation, statistically significant increases in residency applicants matching to a home institution were observed in multiple fields (dermatology, otolaryngology, plastic surgery, and orthopaedic surgery) that are traditionally competitive with the loss of the traditional away rotation format in the year 2021 [17][18][19] .…”
Section: Discussionmentioning
confidence: 98%
“…All 3 studies concluded that lack of face-to-face interaction, such as virtual interviews and lack of away rotations, may have played a role in their observed findings. Although correlation does not equal causation, statistically significant increases in residency applicants matching to a home institution were observed in multiple fields (dermatology, otolaryngology, plastic surgery, and orthopaedic surgery) that are traditionally competitive with the loss of the traditional away rotation format in the year 2021 [17][18][19] .…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies evaluating 2021 match data showed a significant increase in applicants matching at their home institutions compared with previous years. [8][9][10][11][12][13][14][15] The link between these changes and the COVID-19 pandemic has been described in detail. Among students interested in plastic surgery, COVID-19 not only affected the residency application process but also negatively impacted these students' confidence in their medical education.…”
Section: Introductionmentioning
confidence: 99%
“…2 Our findings were reinforced by multiple studies published following the 2021 plastic surgery match cycle, all supporting the conclusion that with changing interview structures and eliminating away sub-internships, rates of medical students matching at home institutions were significantly higher. 3 , 4 , 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%